Sequels of COVID-19 in nephrology. Chronic kidney patients are more prone to hemodialysis need and mortality - Erjola Bolleku; Ermal Likaj; Larisa Shehaj; Ilir Akshija; Edmond Puca; Entela Puca; Xhesi Baci; Alma Idrizi (Journal of Infection in Developing Countries)
Introduction: Acute kidney injury involves inflammation and intrinsic renal damage, and is a common complication of severe coronavirus disease 2019 (COVID-19). Baseline chronic kidney disease (CKD) confers an increased mortality risk. We determined the renal long-term outcomes of COVID-19 in patients with baseline CKD, and the risk factors prompting renal replacement therapy (RRT) initiation and mortality.